A PostgreSQL/PostGIS Implementation for the Sightseeing Tour Planning Problem - Ardiansyah .; Ruslan Rainis (Jurnal Rekayasa Elektrika, 2013)
This article discusses a procedure for finding the best multi stops route for sightseeing tour through a road network. The procedure involves building a database containing nodes and road network in PostgreSQL, calculating the shortest distance between a pair of nodes using pgDijkstra module, and solving the tour problem using a function written in PL/pgSQL. The function was developed based on the Nearest Insertion Algorithm for solving the Travelling Salesman Problem. The algorithm inserts a sightseeing attraction (node) at the best position in the existing route, which is between a pair of nodes that yields the minimum difference between the total tour time before and after the new node was inserted. The test result shows that the function can solve the problem within acceptable runtime for web application for total destination nodes of 22. It is concluded that the whole procedure was suitable for developing Web GIS application that solve the sightseeing tour planning problem.